PERTUMBUHAN AKAR DUAPULUH GENOTIP PADI GOGO PADA KAHATFOSFOR DAN CEKAMAN ALUMINIUM - Tintin Suhartini (BERITA BIOLOGI, 2010)
Phosphorous insufficiency is a limiting factor for rice production. P deficiency in acid soil of tropical regions causing fixation of Al. Because of it, the giving P fertilizers in acid soil become not efficient. To exploit tolerance varieties to P deficiency and Al toxicity are one of the solutions to decrease P fertilizers. The objective of this experiment was to screen twenty upland rice genotypes for P deficiency and Al toxicity, and double stress Al toxicity and P deficiency in culture solution. The experiment was arranged in a split plot design with three replications. The main plots were aluminium treatment (without and 45 ppm Al), the sub plots were P treatments (0 ppm P, 0,5 ppm P, 5 and 10 ppm P) and twenty genotypes of upland rice were sub-sub plot. The root length and root dry weight characters were used to identify genotypes tolerant to P deficiency and Al toxicity. The results indicated that based on the root length character, Sentani and K36-5-1-1-1 were tolerant to Al toxicity and double stress P deficiency and Al toxicity; while based on the root dry weight character, K36-5-1 -1-1 and NIL-C443 were tolerant to P deficiency, Al toxicity and double stress P deficiency.